2022
DOI: 10.3390/plants11172214
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Usefulness of Moringa oleifera Leaf Extract as a Biostimulant to Supplement Synthetic Fertilizers: A Review

Abstract: The extensive use of synthetic chemical fertilizers is associated with environmental pollution and soil degradation. In addition, the high costs of these fertilizers necessitate the search for alternative, eco-friendly and safe natural sources of phytonutrients. The liquid extracted from moringa (Moringa oleifera Lam.) leaves has been used in agriculture to improve the growth and productivity of several crops. The efficacy of moringa leaf extract (MLE) is attributed to its high content of mineral nutrients, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 88 publications
(195 reference statements)
1
11
0
Order By: Relevance
“…In particular, these studies focused on probing the possibility of inhibiting the action of a number of enzymes that are found in common pests. Our work is complementary to the experimental results obtained by Mashamaite et al [12], which showed that some chemicals extracted from natural materials such as plants can be effective compounds as biopesticides. Their work also suggested that compounds such as the (disodium 5 -inosinate and petunidin 3-glucoside), (calcium 5 -guanylate and chlorogenic acid), chlorogenic acid alone, (kaempferol-3,7-di-O-glucoside with hyperoside and delphinidin 3-glucoside), and (myricetin 3 -glucoside and hyperoside), can be used for the development of multitarget bioinsecticides.…”
Section: Introductionsupporting
confidence: 85%
“…In particular, these studies focused on probing the possibility of inhibiting the action of a number of enzymes that are found in common pests. Our work is complementary to the experimental results obtained by Mashamaite et al [12], which showed that some chemicals extracted from natural materials such as plants can be effective compounds as biopesticides. Their work also suggested that compounds such as the (disodium 5 -inosinate and petunidin 3-glucoside), (calcium 5 -guanylate and chlorogenic acid), chlorogenic acid alone, (kaempferol-3,7-di-O-glucoside with hyperoside and delphinidin 3-glucoside), and (myricetin 3 -glucoside and hyperoside), can be used for the development of multitarget bioinsecticides.…”
Section: Introductionsupporting
confidence: 85%
“…As a result of their digestion, livestock, particularly cows, sheep, and goats, produce methane, a GHG [65]. The use of synthetic fertilizers releases nitrous oxide, another potent greenhouse gas, into the atmosphere [66]. Agriculture also contributes to climate change by altering the albedo of the Earth's surface, also known as the reflection of solar radiation [67].…”
Section: Global Climate Change and Public Health Nexusmentioning
confidence: 99%
“…Plant biostimulants are foliar fertilizers that modify the plant's metabolic processes, significantly improving plant growth and production (European Biostimulants Industry Council, 2012;Mashamaite et al, 2022;Azzam et al, 2022). Some growthpromoting materials like antioxidants, osmoprotectants, phytohormones, and nutrients are found in plant extracts such as the seed extract of moringa (Moringa oleifera L.) and the root extract of licorice (Glycyrrhiza glabra) (Desoky et al 2019a;Desoky et al 2019b).…”
Section: Introductionmentioning
confidence: 99%